Changes in Cardiac Responses of Sportsmen from hours of prolonged severe exercise. Issue 3 (December 1972) - Brooke, J. D.; Firth, M.
Abstract : Resting heart rates were obtained hours before and after severe physical exercise performed by racing cyclists on the Tour of the North (Ireland) 1971. With long duration of performance there was elevation of heart rates for up to seven hours post activity, when compared with morning values or with similarly timed post activity measures following short duration performance. Attention is directed to the possible implication of body heat retention or disturbed body water-electrolytes homeostasis. Also noted is the affect of the phenomenon upon the use of resting heart rates for fitness assessment.